2011
DOI: 10.1111/j.1365-3083.2010.02496.x
|View full text |Cite
|
Sign up to set email alerts
|

T Regulatory Cells and Immune Activation in Mycobacterium tuberculosis Infection and the Effect of Preventive Therapy

Abstract: Mycobacterium tuberculosis (TB) often causes persistent infection and many immune cell subsets and regulatory mechanisms may operate throughout the various stages of infection. We have studied dendritic cell (DC) subsets, regulatory T cells (Treg) and the expression of activation and apoptosis markers on CD4+ and CD8+ T cells in blood from patients with active TB (n = 20), subjects with positive QuantiFERON‐TB GOLD (QFT) test (LTBI, latent TB infection) (n = 20) before and after 3 months of preventive anti‐tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 25 publications
6
42
3
Order By: Relevance
“…A significant correlation was not observed for persons with latent M. tuberculosis infection. Our findings differ from a previous study that recently found a positive correlation between Treg cell frequency and the frequency of CD4 ϩ CD38 ϩ HLA-DR ϩ T cells in healthy uninfected controls but not among subjects with active tuberculosis disease or latent M. tuberculosis infection (54). One reason that we may have observed different results could be because we compared immune activation between persons with pulmonary and extrapulmonary tuberculosis, whereas the referenced study combined these two patient groups.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…A significant correlation was not observed for persons with latent M. tuberculosis infection. Our findings differ from a previous study that recently found a positive correlation between Treg cell frequency and the frequency of CD4 ϩ CD38 ϩ HLA-DR ϩ T cells in healthy uninfected controls but not among subjects with active tuberculosis disease or latent M. tuberculosis infection (54). One reason that we may have observed different results could be because we compared immune activation between persons with pulmonary and extrapulmonary tuberculosis, whereas the referenced study combined these two patient groups.…”
Section: Discussioncontrasting
confidence: 55%
“…The perturbation of the immunologic environment during M. tuberculosis infection is felt to contribute to HIV disease severity and progression in coinfected persons (20). Previous studies have reported increased activation of CD4 ϩ and CD8 ϩ T lymphocytes in active tuberculosis and latent infection (4,24,43,44,54). These studies have either studied only persons with pulmonary tuberculosis or evaluated pulmonary and extrapulmonary tuberculosis together as one entity.…”
Section: Discussionmentioning
confidence: 99%
“…While individuals with latent or asymptomatic infection exhibit normal or slightly elevated Treg numbers in their blood [60, 61], those with active TB tend to show increased numbers of Tregs in the blood and at sites of infection (lung and pleural sac) [62-65]. Histological analysis has further shown that cavitating granulomas, those that generally possess the highest bacterial burden, contain significantly more Tregs than other types of granulomas [66].…”
Section: Regulation Of Adaptive Immunity Against Mtbmentioning
confidence: 99%
“…Highly differentiated circulating effector T cells have a limited lifespan (i.e., months) (24) and disappear or greatly decrease after removal of antigen after bacterial clearance and cessation of antigen presentation (i.e., completion of LTBI treatment) (25). Several prior studies have described activated effector T-cell phenotypes in active TB and LTBI in animal models and ex vivo human studies (4,(26)(27)(28)(29)(30)(31)(32). Moreover, antibiotic treatment is known to alter the phenotype and transcriptome of circulating T-lymphocytes in patients with active TB infection, although little is known of the effects after LTBI treatment (31,33).…”
Section: Original Articlementioning
confidence: 99%